Protective effect of Petroselinum crispum extract in abortion using prostadin-induced renal dysfunction in female rats - Maryam Rezazad; Farah Farokhi (Mashhad University of Medical Sciences, 2014)
Objective: Present study investigated the effects of parsley extract on pregnant rat kidneys which have undergone clinical abortion using prostaglandins. The renal protective effect of parsley extract was evaluated in pregnant rats which had an abortion. Parsley was used due to its antioxidant properties. Materials and Methods:  Fifty-four female rats were divided in 9 groups of 6: control pregnant, two pregnant groups which received parsley extract and prostadin, two non-pregnant groups treated with parsley extract and prostadin, a group administered with both treatments, and three groups which received parsley extract in pre-implantation, implantation, and post-implantation periods of embryos. Ethanolic extract (5 mg/kg) was given daily to animals for 18 days of pregnancy period. Parameters such as malondialdehyde (MDA), total antioxidant statues (TAS), creatinine, and urea were measured using biochemical assays. Histopathologic studies were also done with Hematoxylin-Eosin staining method. Results: After 18 days of treatment, significant differences were observed in serum creatinine, urea, and MDA and TAS levels. Kidney cross-sections showed edema in prostadin-treated rats while improvements in parsley + prostadin -treated rats were observed. Conclusion: These results suggested that ethanolic extract of Petroselinum crispum reduced the dysfunction in rats kidney caused by prostadin-induced abortion and could have beneficial effect in reducing the progression of prostaglandin-induced edema.